Pengujian Pengaruh Ketinggian Weir pada Koefisien Discharge dari Weirmeter Sharp-Crested V-Notch 90o - Komarudin Komarudin; Djoko Suprijatmono; Gennady Chitra Pati (Bina Teknika, 2019)
Weirmeter is a discharge gauge on an open-channel flow that is usually applied to dams and rivers. In each weirmeter there is a discharge coefficient (Cd), which is the coefficient multiplied by the theoretical discharge to obtain the actual discharge because the pressure difference and flow velocity are neglected. The Cd is directly proportional to the discharge. The actual debit measurement results do not approximate the result (the multiplication of the theoretical debit with Cd). This difference may be due to unequal Cd values for each weir dimension, one of which is the weir height (P). Therefore it is necessary to test the weirmeter with P varies in order to know the pattern and the value of Cd. The tested weirmeter is sharp-crested v-notch 90o with a length of 200 cm and a width of 35.5 cm. P used is 20.3 cm; 21.3 cm; and 22.3 cm. From the test, the Cd value is inversely proportional to P although some of these test results are far from the theory because it requires a 90% confidence interval on the Student distribution (t distribution). The value of Cd in weirmeter used is 0.6996 for P 20.3 cm; 0.6657 for P 21.3 cm; and 0.5781 for P 22.3 cm.